Implementasi Keterbukaan Informasi Publik Dalam Pengelolaan Keuangan Daerah : Studi di Satuan Kerja Perangkat Daerah Kota Malang - Saverius Dhuri Mbipi (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This research aims to describe regional financial management which includes: planning and budgeting, regional financial accountability; and transparency which includes transparency and accessibility, and the performance of Regional Work Units; analyze the influence of the effectiveness of financial planning, transparency of financial reporting on the performance of Regional Government Work Units. The type of research used is explanatory. The number of samples in this study was 32 respondents. The data collection technique uses a questionnaire in the form of a statement along with an answer score using a Likert scale of 1 to 5. The analysis technique uses descriptive analysis and multiple linear regression analysis. Regional financial management which includes; Transparency and accessibility of regional financial reporting influences the performance of Regional Work Units.